Effect of titanium diboride on the homogeneity of boron carbide ceramic by flash spark plasma sintering. Issue 13 (September 2018) - Wu, Jiawei; Niu, Bo; Zhang, Fan; Lei, Liwen; Zhang, Jinyong; Ren, Lin; Wang, Weimin; Fu, Zhengyi
Abstract: A novel method, namely flash spark plasma sintering (FSPS), combining flash sintering and electric field assisted sintering, was utilized to densify boron carbide/titanium diboride (B4 C/TiB2 ) composites. Further, sintering homogeneity of the composites with different contents of TiB2 was systematically investigated and theoretical model was built. Results indicated that addition of 50 wt% TiB2 led to the densification of B4 C/TiB2 composite by up to 97.7% with regional range 1.9% at 1872 °C under pressure of 4 MPa in 60 s. The preferential pathway of TiB2 network proves to disperse the central current and distribute thermal flow throughout the specimen possibly via tunneling, electronic field emission effect at first stage and lower-resistance composite pathway latter, contributing to the increased homogeneity.